2001
DOI: 10.1159/000049288
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Delayed Memory Performance in Schizophrenia Spectrum Patients: Use of Matched Tasks

Abstract: Rapid forgetting has been observed in long-term schizophrenic patients in the past. In this study, the rate of forgetting was assessed in short-term schizophrenic, schizophreniform and schizoaffective patients who had positive symptoms in the past, and in schizophreniform patients who never had positive symptoms. Four groups of patients representing these distinctions and a group of normal controls were assessed using immediate and delayed recall tasks, while controlling for effects of discriminating power of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Delayed memory is more impaired than immediate recall in schizophrenia (Calev, 2001;Dougherty et al, 1998). Although ceiling effects limits our ability to detect performance changes, Brd1 +/À mice did not differ from WT mice when there was no delay between information and choice runs but where significantly impaired when a delay of 90 s was introduced.…”
Section: Discussionmentioning
confidence: 83%
“…Delayed memory is more impaired than immediate recall in schizophrenia (Calev, 2001;Dougherty et al, 1998). Although ceiling effects limits our ability to detect performance changes, Brd1 +/À mice did not differ from WT mice when there was no delay between information and choice runs but where significantly impaired when a delay of 90 s was introduced.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have consistently demonstrated significant impairments in immediate and delayed memory in both SZ and BD II [ 41 44 ]. In this study, we conducted a correlation analysis between RBANS immediate and delayed memory scores and clinical improvements (PANSS scores for SZ and HAMD scores for BD II).…”
Section: Discussionmentioning
confidence: 99%